2013
DOI: 10.1016/s1836-9553(13)70200-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation cycling has no clear effect on urine output, lower limb swelling, and spasticity in people with spinal cord injury: a randomised cross-over trial

Abstract: ACTRN12611000923965.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…These studies were homogeneous (χ 2 = 2.21; p = 053; I 2 : 0%). The overall effect of ES on spasticity of the lower limbs was non-significant (mean difference: 0.55; 95% CI: −0.31 to 1.41; p = 0.21), although three studies [12,29,30] demonstrated a decrease in spasticity ( Fig. 3).…”
Section: Study Not Included In Meta-analysismentioning
confidence: 95%
See 3 more Smart Citations
“…These studies were homogeneous (χ 2 = 2.21; p = 053; I 2 : 0%). The overall effect of ES on spasticity of the lower limbs was non-significant (mean difference: 0.55; 95% CI: −0.31 to 1.41; p = 0.21), although three studies [12,29,30] demonstrated a decrease in spasticity ( Fig. 3).…”
Section: Study Not Included In Meta-analysismentioning
confidence: 95%
“…Two studies analyzed muscle volume [27,28] and four analyzed spasticity [12,14,29,30]. Four studies recruited patients with cervical and thoracic SCI [12,14,28,30] and two studies selected patients with complete thoracic SCI [27,29]. The duration of time since SCI reported in the studies allowed us to examine the effects of ES on skeletal muscle volume and spasticity in patients with non-chronic versus chronic conditions.…”
Section: Description Of Studies and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 and Figure 1 show the reporting of each CONSORT item. The median (IQR) number of CONSORT items per trial that was 'fully reported' was 11/37 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The median (IQR) number of CONSORT items per trial that was either 'fully reported' or 'not relevant' or 'not reported but unable to determine if relevant/done' was 20/37 items (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%